PENGARUH PENGERINGAN DAN SUHU PENYIMPANAN TERHADAP DAYA HIDUP BUI CITRUS AMBLYCARPA - WULIJARNI, N.; SOETJIPTO, SOETJIPTO (Research Center for Biology-Indonesian Institute of Sciences, 1985)
N. WULIJARNI - SOETJIPTO, 1985. Effect of desiccation and storage temperature on the viability of seeds of Citrus amblycarpa. Berita Biologi 3 (3): 95- 100. Seeds of Citrus amblycarpa (Hassk.) Ochse were dried using several methods. The seeds remained fully viable when the moisture content were reduced to around 5%. Upon storage, those seeds stored at 28°, 10° and 4°C were still viable after 287 days. Further observation showed that storage at 10°, 4° and - 10°C enabled seeds to maintain their germination until the end of the experiment, i.e. 910 days. Therefore, it is concluded that C.amblycarpa seeds tend to follow the behaviour of the orthodox seeds.